THE POTENTIAL OF ICT SMES IN PAKISTAN - Mustafa, Sadaf; Arshad, Muhammad; Moin, Nighat (Archives of Business Research, 2018)
Pakistan has been registering increasing growth rates in its Information Communication and Technology (ICT) sector, with IT exports crossing 2.5 billion mark and registered IT companies surpassing 2000 in number. The growth is mainly powered by service-sector small and medium enterprises (SMEs) of the country, which are subject to little or no regulatory requirements and a lucrative tax amnesty up to June 2019. The information and communication technologies (ICT) sector of Pakistan employs thousands of micro and small firms and self-employed individuals producing various ICT related products and services for domestic and foreign consumption. These small business units may comprise of just an individual, a group of individuals, micro enterprises up to 10 employees and medium sized companies up to 200 employees. The present paper seeks to present, first, the heterogeneous nature of the sector, classifying and comparing enterprises working in it against the prevalent definitions of SMEs. Next, the size and of this SME subset is identified in terms of its consumers, producers, business units and business volumes, with a particular focus on how these together stimulate the economy of the country through increased ICT-based consumption, employment and exports. The paper then analyses some of the challenges and limitations faced by small ICT firms of Pakistan and evaluates whether appropriate measures and initiatives are reflected by ICT and SME stakeholders of Pakistan such as Pakistan Software Exports Board, Pakistan Telecommunications Authority, and SME Development Authority,. The research is exploratory and descriptive in nature. Extensive literature is sought from reputed journals, books, surveys, reports, publications and authoritative web sources targeting service-sector SMEs. The findings of this research hint at major areas of concern and improvement in ICT-based SMEs of Pakistan. They offer great significance for owners, partners, workers and individuals of ICT SMEs as well as government authorities, policymakers and academicians aspiring to strengthen the SME sector.